The Problem of Religious Guidance among Indian Muslims: A Forward-Thinking Proposal - Akhatar, Javed (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
The Indian Muslim community faces a paradox, marked by the presence of religious leaders without a clear path forward. The article identifies a lack of guidance, particularly in matters of faith, as numerous Ulema offer conflicting fatwas, stemming from a flawed Ifta methodology. Tracing the historical evolution of fatwa issuance, the 19th-century shift in India, influenced by the East India Company's trade-focused policies, led to an abundance of independent Ulema. This article explores the historical evolution of Ifta in Islam, with a focus on India. It reviews the transition to formal fatwa institutions, compares practices across regions, and proposes centralizing fatwa authority through a high central council in India, offering recommendations for reform. The absence of a centralized authority for fatwa issuance in India results in a chaotic scenario.To address this, the author proposes a structured solution: establishing a high central council of diverse Ulema and intellectuals. This council would delegate responsibilities for religious and social issues to ensure uniformity in fatwa decisions nationally. However, the article underscores that councils alone are ineffective without legal enforcement authority. This article will show: 1) Abundance of Guidance and Contradictory Fatwas; 2) Evolution of Fatwa Issuance in Islamic History; 3) Current State of Fatwa Issuance and Recommendations for Reform. Additionally, it advocates reevaluating the concepts of 'Dar al-Islam' and 'Dar al-Harb' in the context of India's identity. The author suggests a Parliament-recognized Council to issue fatwas, aligning with democratic principles and reflecting shared ownership among India's diverse Muslim population.